The Regulation of Natural Resources Law in Australia for Indigenous People - Ros Vickers (Faculty of Law, Jambi University, 2019)
Natural resources law in Australia seeks to regulate, protect and conserve natural resources, while providing consideration to the economic value of projects and permit activities to occur. The same environmental laws apply to indigenous peoples as well as other members of the public in Australia. However the recognition of native title rights and sacred sites through legislation can acknowledge the special relationship that indigenous people have with the environment through traditional laws and customs. Indigenous people have a special relationship with their environment that does not easily fall within categories of western values of the environment, and for this reason there is often tension between the common law legal system and indigenous people. While there has been signiﬁcant process working towards a more harmonious regulatory system of natural resources, there is still work to be done. This paper will outline the structure of indigenous rights impacting natural resource regulation in Australia, focusing on the Northern Territory, and will examine the origins of environmental law and indigenous rights